Having Infants in the Family Group Promotes Altruistic Behavior of Marmoset Monkeys - Huang, Junfeng; Cheng, Xiaochun; Zhang, Shikun; Chang, Liangtang; Li, Xuebo; Liang, Zhifeng; Gong, Neng (Current biology, 2020)
The common marmoset (Callithrix jacchus) has attracted much attention as a useful model for studying social behaviors [1–3]. They naturally live in a monogamous family group and exhibit cooperative breeding [4], in which parents and older siblings help to carry infants less than 2 months old [5–7]. Marmoset parents also transfer foods to their offspring, a process that may help them learn the food diet [8]. Furthermore, marmosets show spontaneous altruistic behaviors, such as providing food to non-reciprocating and genetically unrelated individuals [9]. These social habits indicate that marmosets may be a useful non-human primate model for studying parenting and altruistic behaviors, as well as underlying neural mechanisms. Using a novel rescue paradigm, we found that marmoset parents and older siblings showed strong motivation to rescue trapped young infants but not juvenile marmosets beyond 2 months of age, and infant calls alone could trigger these parents’ rescue behaviors. The marmoset parents showed little rescue of each other, but young infants or infant calls could also induce such parents’ mutual rescue. Moreover, all these infant- and mate-rescue behaviors depended on currently having young infants in the family group. Functional MRI studies on awake adult marmosets showed that calls from young infants, but not juvenile marmosets, elicited a large-scale activation of specific brain areas including auditory and insular cortices, and such activation was absent in marmosets not living with infants. Thus, such infant-induced modification of neural activity offers a window for examining the neural basis of altruistic behaviors in marmoset monkeys. •We developed a novel rescue paradigm for studying altruistic behaviors in marmosets•Marmoset parents and older siblings show strong motivation to rescue infants•Having infants in the group promotes infant- and mate-rescue behaviors in marmosets•Having infants alters infant-call-elicited brain activation in marmoset parents Using a novel rescue paradigm, Huang et al. find that marmoset monkeys show altruistic behavior by rescuing trapped group members including young infants and mates. All these rescue behaviors depend on currently having young infants in the group. Furthermore, having infants alters infant-call-elicited brain activation in marmoset parents.